Takhrij and Syarah Hadith of Chemistry: The Perspective of Hadith in Protecting the Environment and Processing Hazardous and Toxic Waste (B3) - Sandi Muhamad Arifin; Muhammad Ilyas; Wahyudin Darmalaksana; Yusuf Rohmatulloh; Hasan Mud'is (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet, rarding sustainable of environment and treating poisoned hazardous waste. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The discussion result of researchis that keeping environment and recycling B3 waste is important, because it prevents the occurrence of fading in live and the environment. The conclusion of this research are takhrij and syarah hadiths of the Prophet. about the harm with chemical analysis proves that environment sustainable and B3 waste recycle is important for human.